Intracranial Aneurysms in Sickle-Cell Disease Are Associated With the Hemoglobin SS Genotype But Not With Moyamoya Syndrome. Issue 7 (July 2016) - Birkeland, Peter; Gardner, Kate; Kesse-Adu, Rachel; Davies, John; Lauritsen, Jens; Rom Poulsen, Frantz; Tolias, Christos M.; Thein, Swee Lay
Abstract : Background and Purpose—: Intracranial aneurysms and aneurysmal subarachnoid hemorrhage may occur more frequently in sickle-cell disease (SCD), and this could be related to the sickle genotype and moyamoya syndrome seen in SCD. Methods—: Records from a total of 1002 patients with SCD attending 2 specialized adult hematologic services were retrospectively reviewed. We analyzed data of a cohort of 767 patients attending 1 SCD clinic between 2002 and 2013 and of 235 patients from the other clinic who have had neurovascular imaging between 2007 and 2014. Results—: We identified 4 patients in the cohort who had an aneurysmal subarachnoid hemorrhage during 9063 patient-years. The highest incidence rate was seen among women in the age group 30 to 39 years with the hemoglobin SS (HbSS) genotype (440 per 100 000 patient-years). Unruptured intracranial aneurysms were found in 20 of the 324 patients, who had imaging data; the prevalence was significantly higher in patients with HbSS genotype compared with other sickle genotypes with the highest prevalence (15%) observed in women in the age group 30 to 39 years. Fifty-one HbSS patients had a moyamoya vasculopathy, but only 3 of these had concomitant intracranial aneurysms. Conclusions—: Intracranial aneurysms are common in HbSS SCD. There was also a trend toward more common occurrence of aneurysmal subarachnoid hemorrhage in HbSS; women in the age group 30 to 39 years were most at risk. There was no correlation between the occurrence of intracranial aneurysms and moyamoya syndrome.